Development of Political Parties and Party Funding: Models and Characteristics - Hrvoje Matakovic; Irena Cajner Mraovic (CES Working Papers, 2015)
The first modern political parties were formed at the end of the 18th century and have, from those times up to now, undergone 4 developing phases; each of the phases is bound to ideal-type political party model: cadre parties, mass parties, catch-all parties and cartel parties. Each of these party models differentiates in various characteristics: party foundation, number of members, and way of leading the election campaigns, but also in ways of financing. This paper describes the above mentioned 4 phases of political parties' development and 4 phases of parties' finances development; it will be analysed in detail positive and negative sides of each of the models of party financing.
Keywords: A1; A2; 330; political parties; political parties financing; corruption